2020
DOI: 10.1136/vr.105621
|View full text |Cite
|
Sign up to set email alerts
|

Developing a 3D animation tool to improve veterinary undergraduate understanding of obstetrical problems in horses

Abstract: BackgroundMany challenges are encountered in both teaching and learning veterinary obstetrics. This may be due to outdated teaching materials, as the main model of content transmission remains centred around text and images.MethodsVisualisation methods such as three-dimensional (3D) and Graphics Interchange Format (GIF) tools were applied in an attempt to improve obstetrics education outcomes in the third-year class. Traditional teaching methods were utilised in the fourth-year and fifth-year students.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Thus, it is clear that the use of the obstetric box and the dummy as a teaching resource contributes to a better understanding of obstetric manoeuvres, a topic of greater complexity in the class, allowing the student to visualize the execution of obstetric manoeuvres and, consequently, increase the student's understanding and confidence to carry out these procedures. This learning contribution was also reported in other studies using alternative teaching resources in theriogenology classes 2,7,8,10,11 …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, it is clear that the use of the obstetric box and the dummy as a teaching resource contributes to a better understanding of obstetric manoeuvres, a topic of greater complexity in the class, allowing the student to visualize the execution of obstetric manoeuvres and, consequently, increase the student's understanding and confidence to carry out these procedures. This learning contribution was also reported in other studies using alternative teaching resources in theriogenology classes 2,7,8,10,11 …”
Section: Discussionsupporting
confidence: 84%
“…Other studies have shown an increase in the learning process using 3D animations to teach obstetric procedures; 2,11 however, the use of the obstetric box and foal dummy make the training more realistic, allowing experiential learning ('learning by doing'). According to Jan et al 8 and Giese et al, 10 the use of anatomical models and dummies also enables a large number of students to practice palpation and obstetric manoeuvres several times without predisposing animals to stress, corroborating with the observations made in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The students, who studied with 3D digital animation scored higher in questions that required spatial ability. 3D animated model of a pregnant horse (Gao et al,200) 30 Veterinary students The use of 3D animated model significantly increased the students' final examination scores. Others 3D tooth morphology quiz (TMQ) app (Lone et al, 2019) 22…”
Section: Undergraduate Health Science Studentsmentioning
confidence: 99%
“…Thirteen studies included in our review collected and analyzed student perception data either from surveys (quantitative data) or focus groups (qualitative data) (Appendix A, Table-4). [25][26][27][28][29][30][31][32][33][34][38][39][40]…”
Section: (Iii) By Correlating Student Performance and Mental Rotation...mentioning
confidence: 99%